EFEK PEMBERIAN NPK DAN BIOTRENT SAWIT TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT - Sirait, Bilter A.; Silalahi, Emeraldo Martupa; Simatupang, Ulina C. Jenni; Manurung, Agnes Imelda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
Oil palm is a mayor commodity crop in Indonesia. This study aims to analyze the effects of NPK fertilizer and Biotrent Sawit liquid organic fertilizer on the growth of oil palm seedlings in a pre-nursery. The research was conducted on Jalan Biola No. 17 Medan, from April to July 2024. A factorial Completely Randomized Design (CRD) was used, with two factors: the first being NPK fertilizer (Phonska) at three levels-P0 = control, P1 = 1.5 g/seedling, and P2 = 3.0 g/seedling; the second factor was the liquid organic fertilizer Biotrent Sawit, applied at three levels-B1 = 1 cc/seedling, B2 = 2 cc/seedling, and B3 = 3 cc/seedling. The variables observed included seedling height, number of leaves, leaf length, leaf width, leaf area, and root volume. The results showed that the NPK (Phonska) fertilizer and Biotrent Sawit liquid organic fertilizer treatments had significant effects on Seedling Height, Leaf Length, Leaf Width, Leaf Area, and Root Volume. However, Treatment had no significant effect on the Number of Leaves in oil palm seedlings. Until the end of the observation period, there was no significant interaction between NPK (Phonska) and Biotrent Sawit liquid organic fertilizer. Generally, higher doses of NPK (Phonska) and Biotrent Sawit liquid organic fertilizer enhanced the growth of oil palm seedlings.